Successful Fluoroscopy-Free Extremity Endovascular Revascularization in an Austere Environment - Reva, Viktor A; Morrison, Jonathan J; Samokhvalov, Igor M (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Background: The use of endovascular techniques in military trauma has increased over time. We present a case of stent-graft placement in a far-forward medical treatment facility (MTF). Methods: A 27-year-old male sustained a blast injury to his upper extremities. He was admitted to a Role 2 MTF 7 hours post-injury. On presentation, he was hemodynamically stable, with multiple closed fractures of both hands, a partial amputation of the right forearm, and the absence of right upper-extremity pulses. Plain radiographs revealed two metallic fragments overlying the right humerus head. The patient underwent a completion below-elbow amputation and right brachial artery exploration. Following the insertion of an arterial sheath, a multipurpose 5-Fr catheter was used to obtain a single-shot angiogram, which demonstrated a traumatic sub-total occlusion of the axillary artery. Using a combination of gentle catheter-wire manipulation and serial radiography, the lesion was traversed and access to normal subclavian artery obtained. A Fluency® Stent-Graft (6 × 100 mm) was then deployed, followed by a completion angiogram, which demonstrated the restoration of extremity perfusion. Results: The patient was evacuated to the next echelon of care on day 5 with good perfusion of the extremity. Computed tomography angiography on day 30 demonstrated thrombotic occlusion of the stent-graft; however, the extremity was viable and further revascularization was not clinically indicated. He was discharged on day 78 following conversion to internal osteosynthesis. Conclusion: Endovascular revascularization of extremity trauma is possible in an austere environment, although techniques need to be refined to support a reduced logistical footprint.